Primaquine toxicity forestalls effective therapeutic management of the endemic malarias. - Baird, J (2012)
Treatment of acutely ill patients, informed by a diagnosis of the species of Plasmodium involved, has long dominated strategic thinking in malaria chemotherapeutics. This bias for both acute illness and access to diagnosis resulted in therapeutic strategies poorly suited to malaria as it occurs in endemic zones. Most of those malarias do not provoke illness and occur beyond diagnostic reach for technical or practical reasons. Therapies effective against all species and stages would likely prove more practical in endemic zones, especially if safely administered without laboratory screening for contraindications. The primary impediment to such therapies is the mild to severe hemolytic toxicity of primaquine in patients with glucose-6-phosphate dehydrogenase deficiency. Primaquine is the only treatment licensed for therapy against relapse caused by dormant liver stages occurring in some species, and against the sexual blood stages responsible for transmission to mosquitoes in all species. Despite being licensed over 50 years ago, no alternative drugs have been developed, and safer dosing regimens of primaquine have not been explored. These failures forestalled the emergence of therapies practical for use in endemic zones, especially in the context of eliminating transmission.